Internalisasi Nilai Kitab Bidayatul Hidayah di Kelas II Tsanawiyah Madrasah Diniyah Haji Ya'qub Lirboyo Kediri - M Rodi (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
The position of value education is vital in the formation of the human person, because humans who have intellectual intelligence as high as any will not benefit positively if they do not have emotional, social, and spiritual affective intelligence. The elimination of the value of education in the curriculum of formal institutions is one of the main causes of the decline in morals and character of the community which is reflected in the high number of crime and immoral acts. The results of the study show that: The Bidayatul Hidayah Book of Learning Process to Class II Santri Tsanawiyah Madrasah Diniyah Haji Ya'qub Lirboyo Kediri has 3 stages: (a) Planning Phase includes 1). Goals to be achieved: Santri can read books, teach and practice and experience positive moral changes, 2). The method used: lecture method, advice, discussion and translating words, 3). Evaluation through written and oral tests. (b) Implementation phase includes 1). The discussion time is at 16.00 WIB, make groups, the other students listen to the leader's explanation, all students discuss. (2) School time at 19.00 WIB, Ustadz interprets words, explains, asks questions about grades. (3) When outside the classroom, the ustadz gives good advice and role models, (c) The evaluation phase includes a written test and an oral test. The process of internalizing the value of the Bidayatul Hidayah Book to Class II Santri Stanawiyah Madrasah Diniyah Haji Ya'qub Lirboyo Kediri there are 3 stages, namely as follows: (a) Value transformation through listening to material at school, the ustadz asks questions about values, discussion (b) Value transactions through ustadz giving role models in class and outside the classroom. (c) Transinternalization through ustadz accompanying students at school, in discussions and in the environment.